2024
DOI: 10.1021/acs.orglett.4c00064
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Quinones to Hydroquinones under Atmospheric Pressure Catalyzed by a Metal–Ligand Bifunctional Iridium Catalyst

Jin Zhang,
Xiangchao Xu,
Guoqiang Zhao
et al.

Abstract: A general method for the hydrogenation of quinones to hydroquinones under atmospheric pressure has been developed. In the presence of [Cp*Ir(2,2′-bpyO)(H 2 O)] (0.5−1 mol %), a range of products were obtained in high yields. Furthemore, the expansion of this catalytic system to the hydrogenation of 1,4-benzoquinone diimines was also presented. Functional groups in the bpy ligand were found to be crucial for the catalytic activity of iridium complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Fujita, Yamaguchi, and co-workers have designed a series of Cp*Ir complexes bearing a bipyridonate or α-hydroxybipyridine ligand, exhibiting highly catalytic activity for acceptorless dehydrogenation of N-heterocycles and alcohols, and hydrogen production from an alcohol–water solution based on the concept of ligand-promoted dehydrogenation. Encouraged by their research, we have also reported that such complexes are effective catalysts for the hydrogen (or deuterium) autotransfer process, acceptorless dehydrogenative cyclization, and hydrogenation and designed a series of new metal–ligand bifunctional catalysts . Chen and Ke’s groups have also reported two Cp*Ir complexes bearing a hydroxybipyridine ligand for the hydrogen autotransfer process .…”
Section: Introductionmentioning
confidence: 99%
“…Fujita, Yamaguchi, and co-workers have designed a series of Cp*Ir complexes bearing a bipyridonate or α-hydroxybipyridine ligand, exhibiting highly catalytic activity for acceptorless dehydrogenation of N-heterocycles and alcohols, and hydrogen production from an alcohol–water solution based on the concept of ligand-promoted dehydrogenation. Encouraged by their research, we have also reported that such complexes are effective catalysts for the hydrogen (or deuterium) autotransfer process, acceptorless dehydrogenative cyclization, and hydrogenation and designed a series of new metal–ligand bifunctional catalysts . Chen and Ke’s groups have also reported two Cp*Ir complexes bearing a hydroxybipyridine ligand for the hydrogen autotransfer process .…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances, most research studies only focus on the N-alkylation of relatively simple reactants bearing a single amino group as nucleophiles. We have reported a series of green reactions based on hydrogen (or deuterium) autotransfer process, acceptorless dehydrogenation, and hydrogenation . In particular, we reported the selective N-alkylation of aminobenzenesulfonamides with alcohols to amino-( N -alkyl)­benzenesulfonamides catalyzed by iridium complex [Cp*IrCl 2 ] 2 and Cp*Ir@CTF (Scheme , left two complexes) .…”
Section: Introductionmentioning
confidence: 99%
“…We developed a series of environmentally benign reactions based on a hydrogen autotransfer process and acceptorless dehydrogenation and hydrogenation using iridium or ruthenium catalysts. In particular, we demonstrated the design and X-ray characterization of an iridium complex bearing a functional 2,2′-bibenzimidazole ligand [Cp*Ir(2,2′-BiBzIm)Cl][Cl] (BiBzIM = bibenzimidazole), and application of it as a homogeneous catalyst for the N -methylation of amines with methanol in the presence of Cs 2 CO 3 (0.3 equiv) (Scheme , left structure) .…”
Section: Introductionmentioning
confidence: 99%